Evaluation of marshall properties of asphalt mixtures with aggregate gradations designed using the bailey method - Mamat, Rosmawati (2008)
This study investigates the properties of asphalt concrete mixtures with aggregate gradations designed using Bailey method and compared with the JKR specification. Bailey method is a systematic approach in blending aggregates with difference gradation (fine aggregate and coarse aggregate) that provides aggregate interlocking as the backbone of the structure and a balanced continuous gradation to complete the mixtures. The Bailey gradation parameter separates the aggregate structure into three gradation namely coarse, medium and fine. This separation were quantified by the decrease in the volume of coarse aggregate in the structure when changing from coarse to fine gradation. The aggregates structures designed using Bailey method were applied in Marshall mix design method to obtain the Marshall properties based on Malaysian Standard and the gradation parameters were compared with the requirement from JKR specification. Two hot mix mixtures considered in this study were Asphalt Concrete Wearing (ACW 14) and Asphalt Concrete Wearing (ACW 10). The mixtures have nominal maximum aggregate sizes (NMAS) of 12.5 mm and 9.5 mm respectively and each sample was compacted using 75 blows per face. The compaction characteristics of the mixtures were analyzed using data from the Marshall Compactor. The value for both VTM and VMA from graph shows when the size of aggregate is smaller (fine aggregate), the percentage of voids in mineral aggregate is low, on the other hand the percentages of VMA and VTM is higher for coarse aggregate.